2016
DOI: 10.1016/j.joca.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary chondrocytes harvested from hips with femoroacetabular impingement

Abstract: hC derived from damaged acetabular and femoral site are qualified for autologous matrix-assisted cartilage transplantation paving the way for cell-based cartilage regeneration in FAI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…These findings suggest that the pattern of expression of selected inflammatory and catabolic markers was not related to a loss of cell viability but to the state of cellular activity, that is, whether cells are producing these proteins. Similarly, previous studies have shown that high chondrocyte viability (87%-95%) was confirmed in delaminated acetabular cartilage 4,23,38 and more than 95% viability in damaged femoral head-neck cartilage in patients with FAI. 4…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings suggest that the pattern of expression of selected inflammatory and catabolic markers was not related to a loss of cell viability but to the state of cellular activity, that is, whether cells are producing these proteins. Similarly, previous studies have shown that high chondrocyte viability (87%-95%) was confirmed in delaminated acetabular cartilage 4,23,38 and more than 95% viability in damaged femoral head-neck cartilage in patients with FAI. 4…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, previous studies have shown that high chondrocyte viability (87%-95%) was confirmed in delaminated acetabular cartilage 4,23,38 and more than 95% viability in damaged femoral head-neck cartilage in patients with FAI. 4…”
Section: Discussionsupporting
confidence: 75%
“…33,42,43 Since FAI was established by Ganz et al 16 as an important etiologic factor for hip OA, various studies on the pathogenesis and pathologic process of hip OA have been conducted. 9,20,36,39 Prevalence of cartilage damage in patients with symptomatic FAI is high, with delamination cartilage lesions observed commonly in the superolateral aspect of the acetabulum (impingement zone) and early degenerative malacia lesions observed in the posterior peripheral rim. 6,27,30 However, the molecular mechanisms by which hip FAI leads to progression of disease resulting in hip OA are not well-understood.…”
mentioning
confidence: 99%
“… 5 , 39 But, encouragingly, the chondrocytes were able to be redifferentiated and maintained differentiation when seeded in tri-dimensional hyaluronan-based hydrogel cultivation, showing high expression levels of Col II and aggrecan, as well as decreased production of IL-1β. 6 Clearly, as shown by these studies and ours, there are varying results for percentage viability in chondral flaps and surrounding tissue. However, the data suggest that these chondrocytes may not be suitable for efficient cartilage regeneration given the tissue quality and microenvironment where they are found.…”
Section: Discussionmentioning
confidence: 60%
“…The authors suggested that the varying amounts of fibrocartilage represented anabolic repairing attempts of a metabolically active tissue due to inflammation. 32 Interestingly, a study by Bretschneider et al, 6 which included 6 patients with cam-type FAI, tested the proliferation and differentiation potential of chondrocytes found in samples retrieved from the anterosuperior acetabulum and the anterolateral head-neck region. The chondrocytes were found to be viable in monolayer expansion after 19 days, reaching viability above 90%.…”
Section: Discussionmentioning
confidence: 99%